Internalization of Islamic Spiritual Programs in Shaping Students' Morals - Makmur, Makmur; Hasis, Pertiwi Kamariah; Rizal, A. (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to describe the process of internalizing the Islamic spiritual program and changes in students' religious behavior at SMA Negeri 2 Palopo City. This study used a qualitative approach with phenomenological methods to understand students' subjective experiences participating in the Islamic spiritual program at SMA Negeri 2 Palopo City, focusing on the internalization of Islamic values ​​and the resulting changes in religious behavior. Data were collected through in-depth interviews, participant observation, and documentation such as journals, reports, and activity photographs, to provide a complete and valid depiction of reality. Data analysis was conducted systematically through reduction, presentation, and drawing conclusions. It was validated using source triangulation and an audit trail to ensure the validity of the findings. The Islamic spiritual program at SMA Negeri 2 Palopo City was successfully internalized by students through structured and ongoing activities, thus encouraging gradual changes in religious behavior. Students experienced a transformation from obedience driven by external pressures, imitating the behavior of teachers or friends, to internalizing Islamic values ​​in their daily lives. Improvements in students' morals were evident in their disciplined worship, patience, honesty, social awareness, self-control, and tolerance towards friends and the school environment. Islamic spiritual programs have proven effective in shaping students' Islamic character holistically through the consistent internalization of religious values ​​in daily practice.